Creating Alignment in Employee Performance Management - Grubi, Arta Koka; Mahmutaj, Lura Rexhepo (European Journal of Economics and Business Studies, 2017)
The current study will identify actions for maximizing the effect of goal development and performance management system to enable enhanced employee performance and motivation. In addition, exceptional consideration is dedicated to the methodological challenges of employee performance management inherent and adopted throughout the years. Quantitative approach will be used to assess the external environment through a comprehensive literature and employee surveys review demonstrating employee evaluation methods. However, the unique characteristic of this research, in proportion to other research, is that data is gathered from primary source. The paper presents “Real Time Employee Evaluation and Bonus Systems.” This is a subject that has not been adequately explored within existing literature. It consists of a practical mechanism which demonstrates how a performance evaluation method is used by a leading Telecom Company in Kosovo (X Telecommunications). We will explore the possibilities and limitations of the performance employee evaluation.